x²+10x+6=0,Solve the given equation using the general formula.
Answers
Answered by
1
x= -b +underroot(b^2-4ac)/2a
x=-b - underroot(b^2-4ac)/2a
x= -10+underroot(76)/2, 10-underroot(76)/2a
Answered by
2
Solution :
Compare given Quadratic equation
x²+10x+6=0 with ax²+bx+c=0, we get
a = 1 , b = 10, c = 6
discreminant (D) = b² - 4ac
= 10² - 4×1×6
= 100 - 24
D = 76
*****†***********************************
We know the quadratic formula:
x = [ -b ± √D ]/(2a)
******************************************
x = [ -10±√76 ]/(2×1)
= ( -10±2√19 )/2
= -5±√19
Therefore
x = -5+√19 or x = 5+√19
••••
Compare given Quadratic equation
x²+10x+6=0 with ax²+bx+c=0, we get
a = 1 , b = 10, c = 6
discreminant (D) = b² - 4ac
= 10² - 4×1×6
= 100 - 24
D = 76
*****†***********************************
We know the quadratic formula:
x = [ -b ± √D ]/(2a)
******************************************
x = [ -10±√76 ]/(2×1)
= ( -10±2√19 )/2
= -5±√19
Therefore
x = -5+√19 or x = 5+√19
••••
Similar questions
Math,
8 months ago
Math,
8 months ago
Chemistry,
8 months ago
Math,
1 year ago
Math,
1 year ago
Social Sciences,
1 year ago
Social Sciences,
1 year ago